2023
DOI: 10.3390/agronomy13071769
|View full text |Cite
|
Sign up to set email alerts
|

The Nitrogen Cycling Key Functional Genes and Related Microbial Bacterial Community α−Diversity Is Determined by Crop Rotation Plans in the Loess Plateau

Abstract: Soil nitrogen cycling microbial communities and functional gene α−diversity indicate soil nitrogen cycling ecological functions and potentials. Crop rotation plans affect soil nitrogen fractions and these indicators. We sequenced soil samples from four crop rotation plans (fallow, winter wheat monoculture, pea-winter wheat-winter wheat-millet rotation, and corn-wheat-wheat-millet rotation) in a long-term field experiment. We examined how microbial communities and functional gene α−diversity changed with soil n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…The observed changing patterns in Menhinick and Margalef indices of the soil communities in the past fire sites were consistent and correlated with the levels of soil TN, AN and MC. Possibly, soil water content and soil nitrogen can promote the increase in some microbial abundance [48,49]. In addition, we found that the Menhinick and Margalef indices in soil of past and more recent moderate fire sites were similar to those of the control sample, which is consistent with the "intermediate disturbance hypothesis theory" proposed by Connell from the point of view of the species richness and diversity of the biological communities [50].…”
Section: Effects Of Forest Fires On Soil Microbial Diversitysupporting
confidence: 86%
“…The observed changing patterns in Menhinick and Margalef indices of the soil communities in the past fire sites were consistent and correlated with the levels of soil TN, AN and MC. Possibly, soil water content and soil nitrogen can promote the increase in some microbial abundance [48,49]. In addition, we found that the Menhinick and Margalef indices in soil of past and more recent moderate fire sites were similar to those of the control sample, which is consistent with the "intermediate disturbance hypothesis theory" proposed by Connell from the point of view of the species richness and diversity of the biological communities [50].…”
Section: Effects Of Forest Fires On Soil Microbial Diversitysupporting
confidence: 86%
“…However, the gene copy numbers associated with N-cycling in the rhizoplane samples exhibited variations across different soil depths, and no disparities were observed between WM and WR. Liu et al (2023) noted that crop rotation is a significant factor influencing nitrogen-cycling functional genes. They found that crop rotation increased the richness of bacterial communities associated with functional genes involved in nitrogen cycling.…”
Section: Monoculture Impacts the Abundance Diversity And Composition ...mentioning
confidence: 99%
“…This observation does not align with existing research in the field. For example, a diversified cropping system has shown positive effects on the soil microbiome, which can be observed by the increase in alpha diversity and expanded network structure in soils under conventional N application (Liu et al, 2023). A meta-analysis conducted by Venter et al (2016) found that higher microbial diversity was generally observed in soils with a greater diversity of crops.…”
Section: Monoculture Impacts the Abundance Diversity And Composition ...mentioning
confidence: 99%
See 2 more Smart Citations